PERKEMBANGAN KOPERASI SIMPAN PINJAM WISUDA GUNA RAHARJA DI KOTA DENPASAR 1981-2014 - Vicilia Samosir, Desy Chafriaty (Humanis; Volume 15. No.2. Mei 2016, 2016)
The purpose of this study are: 1) to know the process of development of Credit Unions Graduation To Prog from the year 1981 to 2014, 2) to understand the dynamics of the development of Credit Unions Graduation To Prog towards improving the economy and society members, and 3) to understand the role and impact Graduation Credit Unions To Prog from year 1981 to 2014. With the presentation of data analysis using quantitative descriptive method. The results obtained from this study are presented dpaat. Growth and development of Credit Unions Graduation To Prog from time to time, the better is due to the cooperative management services provided to its members in accordance with its motto. The presence of Credit Unions Graduation To Prog can improve the economics of its members into a better direction. The forerunner of Credit Unions Graduation To Prog is a small community called Tagura. In the development of Credit Unions Graduation To Prog has ups and downs that gives the impression of a very advanced changes within a financial institution that is healthy and strong professionally, promote togetherness and mensejahterkan members. Purpose of the establishment Credit Unions Graduation order to raise public Prog or more Catholics, the unity and integrity, improve the economic welfare of the people and life members.
Keywords: Tagura, Credit Unions.